A corpus-based investigation of Xhosa English in the classroom setting - Platt, Candice Lee (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2004)
This study is an investigation of Xhosa English as used by teachers in the Grahamstown area of the Eastern Cape. The aims of the study were firstly, to compile a 20 000 word mini-corpus of the spoken English of Xhosa mother-tongue teachers in Grahamstown, and to use this data to describe the characteristics of Xhosa English used in the classroom context; and secondly, to assess the usefulness of a corpus-based approach to a study of this nature. The English of five Xhosa mother-tongue teachers was investigated. These teachers were recorded while teaching in English and the data was then transcribed for analysis. The data was analysed using Wordsmith Tools to investigate patterns in the teachers' language. Grammatical, lexical and discourse patterns were explored based on the findings of other researchers' investigations of Black South African English and Xhosa English. In general, many of the patterns reported in the literature were found in the data, but to a lesser extent than reported in literature which gave quantitative information. Some features not described elsewhere were also found. The corpus-based approach was found to be useful within the limits of pattern-matching.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: English language -- Study and teaching (Foreign speakers) -- South Africa; Computational linguistics; Black English -- South Africa; Black people -- South Africa -- Eastern Cape -- Education